Non-performing loans: evidence from US States / Nur Amira Farahin Abdul Razak - Abdul Razak, Nur Amira Farahin (2017)
This research provides analysis for state level banking industry specific as well as macroeconomic determinants of Non-performing Loans (NPLs) for banks in the North American region of the US States. The sample consists of banks from the state of New York City and Washington D.C from year 2006 until year 2015. There states are chosen because they were some of the states that were affected by the Global Financial Crisis (GFC). The banks chosen is based on the rankings on the bank's total assets. The banks specific variables include Return on Equity (ROE), Net Interest Margin (NIM) and Loan to Deposit ratio (LTD) while the Macroeconomic variables would be the Unemployment rate. Panel Ordinary Least squares (OLS) method is used to analyze the data sample. LTD has a significant negative relationship with NPL which contradicts with results from previous studies. The inverse relationship between LTD and NPL are due to the decrease of NPLs after the subprime crisis.NlM displays a positive relationship towards NPL. The result for ROE shows a significant negative correlation towards NPL while the unemployment rate results show that there is a positive relationship between unemployment and NPL.